Los jóvenes y su participación ciudadana en el centro poblado rural de santo domingo, distrito de laredo, en el año 2012. - Tejada Rolando, Emma Milagros (2013)
The formless present of thesis demonstrates how the social conditions of the young population, between the ages from 18 to 24 years, limit his alternatives of civil participation in the Populated Rural Center of Santo Domingo in the year 2012, these characteristics are given by the negative attitude of the official institutions of the central and local government and the crisis of his identification of his territory propitiate limited modals of citizenship. Besides it demonstrates in this report on the negative attitude of the official institutions that they contribute in order that the young population between the ages from 18 to 24 years of the Populated Rural Center of Santo Domingo, they do not have definite modals of civil participation, for which does not facilitate the fluency of access to the exercise of civil, political, economic and cultural laws, since the paradigm of citizenship limits itself to the participation of the electoral processes by means of the emission of the vote. Other one of the characteristics that one presents is the crisis of his identification of his territory of the young persons of Santo Domingo they propitiate to the ignorance of his place of origin as process of cultural identity, alone which they limit themselves only to the pride and the perception of participation in the development of his community.